Development of a Modified QuEChERS Method Coupled with LC-MS/MS for Determination of Spinetoram Residue in Soybean (Glycine max) and Cotton (Gossypium hirsutum) - Arnab Goon; Chiranjit Kundu; Pritam Ganguly (MDPI AG, 2022)
An analytical method for the quantitative determination of the insecticide spinetoram in cotton and soybean was established and validated using liquid chromatography tandem mass spectrometry (LC-MS/MS). Spinetoram is the mixture of two spinosyns, 3'-O-ethyl-5,6-dihydro spinosyn J and 3'-O-ethyl spinosyn L. The method involves extraction with ethyl acetate followed by dispersive solid phase extraction (dSPE) clean-up with primary secondary amine (PSA), C18 and graphitised carbon black (GCB). The final quantitation of spinetoram was done by using LC-MS/MS with positive electrospray ionization. The method was reproducible (Horwitz ratio (HorRat) < 0.5 at 25 ng g−1) and validated by the analysis of samples spiked at 25, 50 and 100 ng g−1 in soybean, cotton and soil. The recoveries of spinosyns were found to be more than 85% when spiked at different levels. The identities of spinosyns were confirmed by using the ion ratio. A field dissipation study was conducted in soybean and cotton to find out the environmental fate of spinetoram, and samples were analysed following the proposed analytical method. Both isomers were found to be dissipated quickly. The pre-harvest interval of spinetoram was calculated in different substrates.